PENYULUHAN BAHAYA PECANDU NARKOTIKA DAN KORBAN PENYALAHGUNAAN NARKOTIKA - Siregar, Gomgom T. P; Silaban, Rudolf; Sinaga, Lestari Victoria (PKM Maju UDA, 2022)
Narcotics and narcotics addicts after Article 1 Paragraph 6 of the Regulation of the Minister of Health of the Republic of Indonesia Number 2415/Kemenkes/Per/XII/2011 concerning Medical Rehabilitation of Drug Addicts, Abusers and Victims of Narcotics Abuse is someone who accidentally uses narcotics because they are persuaded, deceived, deceived, forced , and/or threatened to use narcotics. Rehabilitation is here to provide protection for addicts and victims of narcotics abuse by giving them the opportunity to recover and continue their lives in society, especially narcotics abuse. The Government has made various efforts to prevent narcotics in Indonesia. This is to prevent the circulation of narcotics and narcotics addicts from becoming more devastating. Based on this, we from the Group 3 KKN Team at Darma Agung University carried out community assistance activities in an effort to formulate narcotics education on the use of narcotics. The aim of implementing this service KKN is to provide knowledge and understanding to the public about the types and dangers of narcotics as well as rehabilitation of narcotics addicts. The expected target in this Community Service Community Service Program is to increase public knowledge about narcotics abuse rehabilitation and provide information to the public about the member institutions involved.